Mapping Multi-Level Policy Incentives for Bioenergy With Carbon Capture and Storage in Sweden - Fridahl, Mathias; Bellamy, Rob; Hansson, Anders; Haikola, Simon (Frontiers in Climate, 2020)
Bioenergy with carbon capture and storage (BECCS) is considered a key mitigation technology in most 1.5–2.0°C compatible climate change mitigation scenarios. Nonetheless, examples of BECCS deployment are lacking internationally. It is widely acknowledged that widespread implementation of this technology requires strong policy enablers, and that such enablers are currently nonexistent. However, the literature lacks a more structured assessment of the “incentive gap” between scenarios with substantive BECCS deployment and existing policy enablers to effectuate BECCS deployment. Sweden, a country with progressive climate policies and particularly good preconditions for BECCS, constitutes a relevant locus for such examinations. The paper asks to what extent and how existing UN, EU, and Swedish climate policy instruments incentivize BECCS research, development, demonstration, and deployment in Sweden. The analysis is followed by a tentative discussion of needs for policy reform to improve the effectiveness of climate policy in delivering BECCS. Drawing on a tripartite typology of policy instruments (economic, regulatory, and informational) and the ability of these instruments to create supply-push or demand-pull, the article finds that: 1) no instruments create a demand-pull to cover operational expenditure; 2) economic instruments provide partial support for research and the capital expenditure associated with demonstration, and; 3) regulatory instruments provide partial clarity on environmental safeguards and responsibilities. A few regulatory barriers also continue to counteract deployment. The article concludes that the existing policy mix requires considerable reform if BECCS is to contribute substantially to the Swedish target for net-zero emissions. Continued effort to dismantle regulatory barriers must be complemented with a strong demand-pull instrument that complements the current focus on supply-push incentives. If unreformed, the existing policy mix will most likely lead to substantial public expenditure on BECCS research, development, and demonstration without leading to any substantial deployment and diffusion.